An ethnicity discussed:Legal status and the realization of language rights among Kashubians in Poland - OleksandrVasiukov (Політичні дослідження, 2022)
This article is focused on the study of the current legal status of the Kashubian minority in Poland. The Kashubians are a West Slavic minority ethnic group that was recognized as a regional language community in 2005. Based on the materials collected during a long-term ethnographic fieldwork in places of compact settlement of ethnic Kashubians, the author analyzes the experience of realization of language rights among Kashubians and the community’s perception of the state ethnic policy. As this study will show, language recognition, which has been perceived initially by regionalists in Kashubia as a victory, is now criticized more and more by members of the ethnic group. The processes of rapid language assimilation among Kashubians provoke ethnic activists to rethink their current legal status and seek to increase it by recognizing the Kashubians as a separate people or ethnic minority in Poland. As the materials of this article show, today the possibility of such recognition is hotly debated by the Kashubians and causes disputing attitudes both inside and outside the community. At the same time, the analysis of the sociolinguistic status of the Kashubian language presented in the article shows that language remains a key marker of Kashubian ethnic self-determination, though the regional activist community is gradually debating a possible change in the conceptualization of Kashubian society, its transformation from linguistic to the cultural community. Meanwhile the ideology of the Kashubian language revival coexists with bilingual or predominantly Polish-speaking practices of ethnic activism.